Pengaruh Game Based Learning Berbasis Dimensi Kolaborasi 21CLD Terhadap Kompetensi Kolaborasi Siswa SMA - Meyssa Dwi Rigawati; Sistiana Windyariani; Siti Neneng Nurhasanah; Gina Nuranti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to see the influence of game-based learning on the 21CLD dimension on high school students' collaboration competence on the concept of movement systems. The study employed a quasi-experimental method, utilizing a Pretest-Posttest Nonequivalent Control Group Design. The sample for this research was 70 students from SMAN 1 Cikembar class XI. The instruments used were collaboration competency questionnaires, student collaboration activity observation sheets, and student response questionnaires. The research results showed that the N-Gain value of collaboration competence in the experimental class was better than the control class with a value of 0.62 in the medium category and 0.29 in the low category. Judging from the hypothesis test, it is significantly different with a sig (2-tailed) value of <0.001 so that the hypothesis H0 is not accepted while H1 is accepted. The conclusion of this research states that the game-based learning model based on the 21CLD collaboration dimension has an effect on students' collaboration competence. Keywords: Game Based Learning, Collaboration Competencies, 21CLD